The 2025 IUMS Fatwa on Israeli Aggression in Gaza: Examining the Muslim-Majority Countries’ Foreign Policy through Maqasid al-Shari'a and Political Realism - Abubakar, Ismail Yau; Mohammed Milad, Ashraf Jomah; Abubakar Muhammad Babayya; Rida Luthfiana Wakhidah (Tuah Foundation, 2025)
This article examines the gap between Islamic legal norms and the foreign policy practices of Muslim-majority countries by analyzing the case of the International Union of Muslim Scholars (IUMS) fatwa regarding Israeli aggression in Gaza in 2025. The fatwa sets forth fifteen directives, including calls for jihād, a total boycott, the cessation of normalization with Israel, and the formation of a military alliance among Muslim-majority countries. In practice, however, most Muslim-majority countries—such as the UAE, Qatar, Saudi Arabia, Egypt, Morocco, and Turkey—continue to maintain diplomatic and economic relations with Israel and its allies. Therefore, this article investigates why the 2025 IUMS fatwa, as a representation of Islamic legal ideals within the framework of maqāṣid al-sharīʿa, has had only limited influence on the foreign policy responses of Muslim-majority countries, which are largely shaped by the principles of political realism. The research employs a qualitative approach, utilizing content analysis of the fatwa text and comparative policy analysis of the foreign policies of those Muslim-majority countries, focusing on diplomatic, economic, and security-related responses based on official statements, agreements, and documented actions. The findings demonstrate that geopolitical, security, and economic considerations are more dominant than commitment to Islamic legal principles, thereby explaining the weak influence of the fatwa on Muslim-majority countries’ policies. The implications of this research affirm the necessity of an integrative approach that connects Islamic legal norms with international political realities, so that strategic fatwas do not remain merely within the moral-normative realm but can be operationalized into realistic and effective foreign policies.